Nutrient leaching in oil palm plantation: a review on special reference to fertilization application - Sham, Isma Nadia; Yap, Chee Kong; Nulit, Rosimah; Peng, Shih Hao Tony; Chai, Ee Wen (Elite Scientific Publications, 2024)
This paper provides overview of the leaching challenges frequently encountered in Malaysian oil palm plantations. The oil palm (Elaeis guineensis) is a vital cash crop extensively grown in tropical regions like Malaysia, a major global palm oil producer. Given Malaysia’s highly weathered and less fertile soil, efficient fertilization is essential to ensure optimal oil palm growth and yield which requires a substantial supply of soluble Nitrogen and Potassium for crop uptake. Malaysia is a tropical country and typically experiences annual rainfall exceeding 2, 500mm, leading to inevitable leaching issues that impact the environment. In this review, five key aspects related to leaching problems were identified. Firstly, groundwater pollution is a concern. Runoff and deep percolation beyond the root zone can carry significant amounts of soluble plant nutrients, posing health risks when entering local community water sources due to high nitrate content. Secondly, nutrient leaching from oil palm plantations can harm freshwater systems by contributing to Nitrate Nitrogen (NO3—N) loads that can trigger surface water eutrophication, leading to algal blooms and disruptions to aquatic ecosystems. Next, intensive management of oil palm plantations can result in nutrient leaching that negatively impacts soil quality and fertility. In turn, it can reduce soil organic matter content and natural biodiversity. Excessive leaching may also hinder efficient nutrient absorption by crops, potentially causing nutrient deficiencies, manifesting as visual symptoms like necrosis and stunted growth. Lastly, if nutrients are not retained in the soil, the land can become toxic and unsuitable for future use unless a sustainable replacement strategy is employed.